Evaluation of Regional Government Financial Performance through a Financial Ratio Approach: An Empirical Study in Jayawijaya Regency 2013–2023 - Abraham Busiara; Mesak Iek; Halomoan Hutajulu (Business Management, 2025)
This study analyzes the financial performance of the Jayawijaya Regency Government from 2013 to 2023 using key financial ratios: autonomy, effectiveness, growth, and efficiency. The research employs a mixed-method approach, combining quantitative analysis of budget realization data with qualitative insights from key informants. The results show that while the effectiveness of locally generated revenue (PAD) was high averaging 166.38% the autonomy ratio remained critically low at 6.44%, reflecting substantial dependence on central transfers. Growth in revenue and expenditure was also suboptimal, falling below 30%, while efficiency ratios hovered around 99%, indicating limited fiscal flexibility. Strategic responses identified include digital tax reform, diversification of PAD sources, and creation of local enterprises. Despite promising policy directions, structural limitations such as geographic isolation and administrative capacity remain major obstacles. The study concludes that sustainable fiscal management in special autonomy regions requires not only technical effectiveness but also systemic reforms in institutional governance and local economic empowerment. The findings offer a valuable reference for policymakers seeking to enhance regional financial resilience in Indonesia's decentralized governance framework.